2√3(√5-1)(√5+1)+(2√3+2)
Răspunsuri la întrebare
Răspuns de
0
2√3(√5-1)(√5+1)+(2√3+2)=
2√15×√5+2√15-2√3×√5+2=2√15×2+2√15-2√3×√5+2=2√75+2√15-2√3×√5+2=2×5√3+2√15-2√3×√5+2=10√3+2√15-2√15+2=10√3+0+2=10√2+2=19,32
2√15×√5+2√15-2√3×√5+2=2√15×2+2√15-2√3×√5+2=2√75+2√15-2√3×√5+2=2×5√3+2√15-2√3×√5+2=10√3+2√15-2√15+2=10√3+0+2=10√2+2=19,32
Răspuns de
0
2√3(√5-1)(√5+1)+(2√3+2)=
2√3*(5-1)+2√3+2=
2√3*4+2√3+2=
8√3+2√3+2=
10√3+2
2√3*(5-1)+2√3+2=
2√3*4+2√3+2=
8√3+2√3+2=
10√3+2
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă